Immunoblot as a potential diagnostic tool for myofibrillar myopathies. Issue 24 (20th October 2015) - Marini, Matteo; Guglielmi, Valeria; Faulkner, Georgine; Piffer, Silvio; Tomelleri, Giuliano; Vattemi, Gaetano
Abstract : Myofibrillar myopathies (MFMs) are a group of inherited or sporadic neuromuscular disorders morphologically characterized by foci of myofibril dissolution, disintegration of the Z‐disk, and insoluble protein aggregates within the muscle fibers. The diagnosis is based on muscle biopsy. Light and electron microscopy has a central role in the diagnostic work up, and immunohistochemistry shows abnormal deposition of several proteins including αB‐crystallin, desmin, and myotilin. In contrast, immunoblotting does not have any diagnostic value because it does not highlight differences in the amount of involved proteins. We investigated the pattern and level expression of desmin, αB‐crystallin, myotilin, and ZASP (Z‐band alternatively spliced PDZ motif‐containing protein) in muscle of seven patients with MFMs by immunoblotting after SDS‐PAGE and 2D‐PAGE using two different solubilizing solutions, one radioimmunoprecipitation assay (RIPA) buffer, and the other urea‐containing buffer. Our data demonstrated that urea‐containing buffer improves the solubilization and recovery of desmin, αB‐crystallin, myotilin, and ZASP as compared with RIPA buffer and that the total content of these proteins is increased in muscles of patients. The present results provide evidence that immunoblotting is an additional tool for confirming diagnosis of MFMs.